(3GdfgGjI aj TQM GdgOGjI ddeQZjfGfis - (3GdMSjf Hf Ydj Hf MLGL Hf Ydj, MSGe GdOjf GdpqSrZnfGbj , J (B711 (3g` s; (3Ydj Hf CHj HcQ Hf YHO GdLdjd GdaQZGfj GdeQZjfGfj, CHh GdMSf HQgGf GdOjf,J (B593 (3g` s
(3ChdgG (B:s
(3cJGH GdWgGQI s
(3BNQgG (B:s
(3cJGH GdfcGM s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdMfajs